2017
DOI: 10.1148/rg.2017160119
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Orbital Emergencies: A Pictorial Review

Abstract: Imaging of the orbit plays an important role in the workup of orbital emergencies. Orbital imaging is particularly useful in the emergency department, where clinical history and physical examination may be limited or delayed until the exclusion or treatment of more life-threatening conditions. Cross-sectional orbital imaging with multidetector computed tomography (CT) and magnetic resonance (MR) imaging is commonly performed in addition to ultrasonography. In an emergent setting, CT is the preferred modality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 45 publications
1
31
0
10
Order By: Relevance
“…Ultrasonography is another alternative imaging method to diagnose inflammation or tumors of the globe in selected cases, but the technique is operator dependent and shows limited capacity in the evaluation of the retrobulbar structures [ 12 , 13 ].…”
Section: Imaging Protocolsmentioning
confidence: 99%
“…Ultrasonography is another alternative imaging method to diagnose inflammation or tumors of the globe in selected cases, but the technique is operator dependent and shows limited capacity in the evaluation of the retrobulbar structures [ 12 , 13 ].…”
Section: Imaging Protocolsmentioning
confidence: 99%
“…Lastly, a full paper review of all eight of the selected articles was performed, which led to the selection of five articles to be utilized in the final review. [2][3][4][5][6] Of the orbital CT evaluation approaches, the BALPINE method was determined to be the simplest to implement, while still being comprehensive. 7,8 To test the effectiveness of the CT evaluation method, an examination composed of CT orbital images was developed with the aid of the Ophthalmology and Radiology departments at San Antonio Uniformed Services Health Education Consortium (SAUSHEC).…”
Section: Methodsmentioning
confidence: 99%
“…Since 1985, efforts have been made through studies and publications to create a systematic approach for ophthalmologists to use when evaluating CT scans. [2][3][4][5][6] One study showed that various CT findings could be used to predict treatment and surgical management of orbital injuries. 7 Despite these efforts, no approach has been widely adopted by ophthalmologists or used to teach residents.…”
mentioning
confidence: 99%
“…Intraorbital spread from ethmoid and frontal ARS is the most common complication and may present as cellulitis, subperiosteal or intraorbital phlegmon and abscess, and lateral displacement of the medial rectus muscle (Figure 6a and b). The clinical presentation may be forward protrusion of the eyeball, proptosis [8][9][10].…”
Section: Acute Rhinosinusitis and Complicationsmentioning
confidence: 99%